A new QEXAFS system on the general XAFS beamline at the Shanghai Synchrotron Radiation Facility - Yongnian Zhou; Songqi Gu; Ying Zhao; Zheng Jiang; Zhaohong Zhang (Journal of Synchrotron Radiation, 2022)
A new quick-scanning extended X-ray absorption fine-structure (QEXAFS) system for in situ studies has been developed and tested on the general XAFS beamline at the Shanghai Synchrotron Radiation Facility. In the new system, an analog-to-digital converter (ADC) with 1 MHz sampling rate is used to acquire the detector data while one scaler is used to precisely calculate the scanning energy. Two external hardware trigger signals were adopted to synchronize the data collection of the ADC and the scaler. The software development platforms of the double-crystal monochromator control system and the new QEXAFS system have been unified with the Experimental Physics and Industrial Control System. By comparing the spectra acquired by the conventional step-by-step XAFS system with an energy range of 1200 eV at the 7.5um Cu foil K-edge, the new system demonstrates satisfactory signal-to-noise ratio and energy resolution. The previous shortcomings, including distortion of the spectrum and energy shift, have been overcome. The tests with different integration times indicated that appropriate parameters not only ensure good experimental results but also enhance the smoothness of the XAFS spectrum at high energy zones. The reliability of the new system has also been verified.